Domestic airborne black carbon and exhaled nitric oxide in children in NYC - Cornell, Alexandra G. (2012)
Differential exposure to combustion by-products and allergens may partially explain the marked disparity in asthma prevalence (3%–18%) among New York City neighborhoods. Subclinical changes in airway inflammation can be measured by fractional exhaled nitric oxide (FeNO). FeNO could be used to test independent effects of these environmental exposures on airway inflammation. Seven and eight year-old children from neighborhoods with lower (range 3–9%, n=119) and higher (range 11–18%, n=121) asthma prevalence participated in an asthma case-control study. During home visits, FeNO was measured, and samples of bed dust (allergens) and air (black carbon) were collected. Neighborhood built-environment characteristics were assessed for the 500m surrounding participants’ homes. Airborne black carbon concentrations in homes correlated with neighborhood asthma prevalence (P<0.001) and neighborhood densities of truck routes (P<0.001) and buildings burning residual oil (P<0.001). FeNO concentrations were higher among asthmatics with compared to asthmatics without frequent wheeze (≥4 times/year) (P=0.002). FeNO concentrations correlated with domestic black carbon among children without seroatopy (P=0.012) and with dust mite allergen among children with seroatopy (P=0.020). The association between airborne black carbon in homes and both neighborhood asthma prevalence and FeNO suggest that further public health interventions on truck emissions standards and residual oil use are warranted.